PERANCANGAN IDENTITAS VISUAL PADA PRODUK UMKM KACANG MANIS OOPA UNTUK MENDUKUNG BRAND REFRESHMENT - Kelvin Falencio; Yonky Pernando; Musliadi KH (Journal of Digital Ecosystem for Natural Sustainability, 2026)
OOPA Sweet Nuts, a Batam MSME, faces obstacles entering modern retail due to packaging and visual identity limitations, specifically lacking essential product information and an optimized logo. This research aims to rebrand the product through a visual identity and packaging refresh, creating a more structured and attractive communication medium. Utilizing the ADDIE model and a Human-Centered Design (HCD) approach, the design process involved digitizing the logo into a vector format, developing a circular badge system, and redesigning the stand-up pouch layout using a grid system with a transparent window. The design was evaluated through media expert validation for feasibility, alongside User Acceptance Testing (UAT) with 30 respondents to measure acceptance. The research yielded a standardized, functional packaging and visual identity ready for printing. This redesign strengthens the packaging's communicative function, increasing brand competitiveness and awareness. Future research should test the design's market effectiveness regarding consumer purchase intention and explore applications in digital promotional media.